PELAKSANAAN PELIMPAHAN SEBAGIAN KEWENANGAN DARI BUPATI KEPADA CAMAT BIDANG PEKERJAAN UMUM DI KECAMATAN MEMPURA KABUPATEN SIAK TAHUN 2011-2012 - Hidayat, Rian; Yusri, Ali (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
In applying the policy in the era of regional autonomy in accordance withthe Local Government legislation, it is necessary to do Delegation of Authority ofHeads of Regional Most officials below it in order to assist the implementation ofthe tasks entrusted with running the Administration greater. According to theDecree of the Minister of Home Affairs No. 138-270 of 2010 on Guidelinesguidelines the District Integrated Services Administration (PATENT), portionmelimpahakan Siak district to sub-district authority Regents to implement localgovernment affairs through Siak regent Regulation No. 42 Year 2011. Thepurpose of this study was to determine the Implementation and inhibiting factorsDelegation of Authority of Regents To the sub-district in the district of the Fieldof Public Works Mempura Siak 2011-2012. Where in assessing theimplementation of the devolution of authority can be reviewed through theanalysis and standardization activities, description and standardization activities,the measurement of the extent of the changes observed and determine the changesobserved.This research was conducted in the district in which the Siak Mempuraselected respondents came from the District Administrative Mempura VillageChief Data collection and research conducted by interview and questionnaires tothe respondents. Once the data is collected and then elaborated by descriptivemethods.From the results of the study found that the majority Delegation ofAuthority Implementation of Regents To the sub-district in District Mempura Siakis rated Not Succeed Neither the percentage of 62%, while the indicatorSuccessfully Neither the percentage 25%. Where these indicators have substandard indicators, assessment and evaluation. From interviews also found thatthe barriers to the implementation of this delegation of authority is still a lack ofpersonnel sub-district government officials and the lack pasrtisipasi mempuracommunity in supporting the implementation of the devolution of authority.Keywords: Planning, Employee competence, participation